Drug resistance profiles in patients attending to an HIV clinic in Quito: a pilot study - Paulina Quirola Amores; Pablo Espinosa; Nelson Cevallos; Enrique Teran (ACI Avances en Ciencias e Ingenierías, 2025)
HIV/AIDS is one of the most important chronic infectious diseases. Although ART therapies decreased morbidity and mortality considerably, new cases continue to appear. HIV-1 drug resistance is one of the most important problems that delay 95-95-95 goals. The presence of drug resistance mutations in naïve and ART-experienced patients is considered a risk factor for treatment failure and the transmission of HIV-1 resistance strains. A cross-sectional study included naïve and ART-experienced patients from one health care center in Quito-Ecuador in 2019 and 2021. Demographic data was collected with blood samples for sequencing, genotyping, and resistance tests. In 42 patients recruited, the overall prevalence of HIV-1 DRM was 9.5%, most related to NNRTI. A total of 42 mutations were found, 38.6% related to PIs, 34.09% to NNRTI/NRTIs, and 22.7% to INSTIs, most of them considered as minor or accessories, producing PLLR, LLR, and in one patient, HLR to NNRTIs. Although few drug resistance mutations that reduce ART susceptibility were identified, further studies are required to characterize HIV-1 drug resistance in Ecuador and its implications for clinical response.